Detection of Gastrointestinal Parasites of Cats and Dogs in Basrah Province - Nadia Thamer; Suhair Al-Idreesi; Noor Farhood (Basrah Journal of Veterinary Research)
The present study has been conducted for the detection of gastrointestinal parasites isolated from cats and dogs in Basrah province from November 2018 to January 2019. One hundred fecal samples were collected from cats and dogs. Samples were submitted to the parasite’s lab in college of veterinary medicine of Basrah university. for diagnoses by direct microscopic examination and concentration methods. Gastrointestinal parasites of cat identified in this study were: Toxascaris leonine 58.8%, Toxoplasma gondii 11.7, Isospora spp   11.7%, Entamoeba spp.17.6% , and for dog were Dipylidium caninum 21%, Toxocara canis 10.5%, Isospora canis 36.8%, Cryptosporidium spp. 5.2%, Giardia spp. 10.5%, Entamoeba spp. 5.2% , Ancylostoma caninum 10.5%,